Thematic Analysis of Produce Packinghouse Sanitation: Challenges and Recommendations Based on Operator and Educator Insights - Allyson N. Hamilton; Sahaana Chandran; Kristen E. Gibson; Juan Moreira (Journal of Food Protection)
Ensuring food safety in produce packinghouses is vital for preventing foodborne illnesses and safeguarding public health. This study identifies cleaning and sanitation challenges within packinghouse environments through thematic analysis of interviews with produce safety educators (N = 21) and packinghouse operators (N = 15). Key challenges include resource limitations, knowledge gaps, outdated equipment, language barriers, and reluctance to invest in change. Small-scale growers often struggle with access to essential tools and supplies, while others may lack foundational knowledge regarding proper cleaning and sanitizing techniques. High employee turnover further complicates consistent training efforts. Language barriers hinder effective communication, particularly among non-English speaking workers and growers. In addition, reluctance or even the inability to invest in change can obstruct the adoption of improved practices. The study highlights specific contamination risks linked with common food-contact surfaces, such as wood, plastic, and stainless steel along with foam rollers, brushes, and rubber surfaces. Cleaning practices vary significantly, ranging from power washing and alcohol wipes to scrubbing with dish soap and steam cleaning. Sanitizers including chlorine, quaternary ammonium compounds, and peroxyacetic acid are frequently employed. Verification of cleaning effectiveness often relies on visual inspection rather than standardized methods such as environmental monitoring or Adenosine Triphosphate (ATP) testing. Recommendations based on these findings include developing clear, accessible training materials, enhancing communication for consistent messaging regarding cleaning and sanitation practices, and investing in research for more effective cleaning technologies and durable food-contact surfaces.